Groundwater flow in carbonate basin facies: the test area of Mount Campo (Molise, southern Italy) - Allocca, Vincenzo; Celico, Fulvi; De vita, Pantaleone; Fabbrocino, Silvia (Italian journal of engineering geology and environment, 2006)
The research has been focused on the hydrogeological behaviour of the basin facies carbonate aquifers that largely outcrop in the Molise region (southern Italy) and are mainly constituted of limestone, cherty limestone and marls. This kind of aquifers, differently from the ones constituted by carbonate platform series, knownly formed by karst limestone, dolomitic-limestone and dolomite, has never been studied in the past, even if they represent the main drinking water resource for the Molise region. The analysis of the groundwater regime is the main method applied in this study, thus the influences given by diffuse infiltration of rainfall or by concentrated infiltration of runoff in karst areas have been investigated.The sample area that we have analysed corresponds to the Mount Campo carbonate mountain (Isernia, Molise). The boundaries of the carbonate aquifer have been defined by means of geological surveys, geophysical and borehole investigations. Such explorations allowed recognising the hydrogeological continuity between the Mount Pasquale-Abeti Soprani structure and the neighbouring carbonate mountains, represented by Mount Campo s.s, Mount S. Nicola and Mount Cerro.The Mount Campo carbonate aquifer shows the existence both of a basal and of a perched groundwater flows. The latter is mainly due to the existence of low permeability interbeds within the carbonate series, even if the surficial karst system could also play an important role according to its variable thickness and development grade. The Fonte Quarto basal spring is characterized by a variable regime, which has shown a sequence of numerous recharge and recession phases during the monitoring period. The variability of spring discharges is strictly dependent by the temporal rainfall pattern and it is influenced by the characteristics of the vadose zone (thick about 100 meters, in average). The groundwater flow generally shows variations beginning from few days (about 4) after rainfall events. This experimental observation is not in agreement with the hypothetical effect due to quick influx of runoff through karst conduits, directly interconnected with the spring. Differently, the sequence of discharge spikes can be mainly related to diffuse infiltration of precipitations within the network of discontinuities. Taking into account the thickness of the vadose zone, the average time lag, between rainfalls and increase of spring discharges, indicates infiltration velocities of about 22 m/d. Such a value is slightly lower than those calculated in the other carbonate aquifers of the central-southern Italy and it can be related to the existence of low permeability interbeds within the vadose zone rather than of low permeability mantling overburdens. Differently, the pumping tests carried out close to the basal spring have shown a transmissivity of 3.0×10-2 m2/s and a storage coefficient of 3.1×10-2, similar to typical values determined for limestone aquifers. This result has been inferred as indicative of the local absence of low permeability interbeds in the saturated zone. The different behaviour between the saturation and vadose zones is confirmed by the different stratigraphic characters of the carbonate series, which presents lower permeability marly interbeds in the upper part. A further validation of the hydrogeological model has been achieved by the hydrogeochemical and isotopic analyses of groundwater.